e-health – expectations and reality - Sikorski, Leszek (Przewodnik Lekarza/Guide for GPs, 2007)
The aim of the study is to present selected aspects of e-health issues in Poland, concentrating on elements discussed very briefly or not discussed at all in Polish literature so far. The study analyzes: • selected aspects of relationships between information society and health care, • the basic goals of the European Union as regards health care and IT in health care, • methods for evaluating goals in telemedicine, • the key priorities for IT in health care in Poland, • selected aspects related to IT standardization in health care, • the content of the main projects related to health care included in the National Computerization Plan.